Public Relations Education at the Crossroad: Trend and Realities. - Ahmad FIPR, PhD., Jamilah Hj.; Putra, MA, I Gusti Ngurah (Jurnal ILMU KOMUNIKASI, 2008)
Abstract: This paper explores the issues of public relations academics credentials on teaching public relations at undergraduate level. Generally, most Asian universities look to the United States education system as the ideal model in developing their own curricula, and frequently invite American professors as visiting fellows to help set up their programmes. In addition, Asian universities, including those in Malaysia and Indonesia still harbour the view that the US offers the best public relations education and practices, and therefore follow the US model regarding any matters related to curriculum, study materials, teaching modules, learning resources and the structure of exam papers. Whilst seeming efficient, as the US leads the fields of public relations, it appears to be done blindly without considering such variables as the encompassing political, economic, legal, media and cultural factors of the society adapting these curricula that should determine the roles and functions of public relations practitioners in any given country. This paper concludes that US still offers the best public relations education in comparison to any Asian universities due to lack of academic credentials.